DIGITAL MARKETING STRATEGY FOR CREATIVE STARTUPS: CASE STUDY - Tjong, Mardi Hartanto; Susiang, Maria Imelda Novita (Journal of Social Entrepreneurship and Creative Technology, 2025)
The rapid growth of digital technologies has transformed the way businesses market their products and services. For creative startups, adopting effective digital marketing strategies is crucial to establish brand identity, attract customers, and achieve sustainable growth. However, many creative startups face challenges in selecting and implementing the most effective digital marketing approaches due to limited resources and expertise. This research aims to explore the digital marketing strategies employed by creative startups and assess their impact on business growth. The study uses a case study approach, focusing on five creative startups across different sectors (design, media, fashion, arts, and entertainment). Data was collected through in-depth interviews with founders and key marketing personnel, along with an analysis of digital marketing campaigns and outcomes. Findings indicate that successful creative startups utilize a combination of social media marketing, content creation, and influencer partnerships to enhance brand visibility and engagement. Additionally, effective use of data analytics to track customer behavior and tailor marketing efforts was found to significantly improve campaign success. The study concludes that adopting a targeted and adaptable digital marketing strategy, coupled with leveraging emerging platforms and data insights, is essential for creative startups to thrive in a competitive market. This research contributes to the growing understanding of digital marketing strategies tailored to the specific needs of creative startups.